2017
DOI: 10.1007/s11356-017-9314-9
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Bacillus amyloliquefaciens as biocontrol agent to fight fungal diseases of maize under tropical climates: from lab to field assays in south Kivu

Abstract: In the province of South Kivu (Democratic Republic of Congo), warm and humid climatic conditions favor the development and spreading of phytopathogens. The resulting diseases cause important losses in production both in crop and after harvest. In this study, we wanted to evaluate the potential of Bacillus amyloliquefaciens as biocontrol agent to fight some newly isolated endemic fungal pathogens infesting maize. The strain S499 has been selected based on its high in vitro antagonistic activity correlating with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…The addition of HSB1 and FZB42 before or after F. oxysporum inoculation significantly reduced DI and DS in wolfberry seedlings. Several studies reported the efficient application of Bacillus species as BCAs in the suppression of different pathogens causing diseases in plants ( Zhang and Xue, 2010 ; Zhao et al, 2017 ; Kulimushi et al, 2018 ; Gautam et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The addition of HSB1 and FZB42 before or after F. oxysporum inoculation significantly reduced DI and DS in wolfberry seedlings. Several studies reported the efficient application of Bacillus species as BCAs in the suppression of different pathogens causing diseases in plants ( Zhang and Xue, 2010 ; Zhao et al, 2017 ; Kulimushi et al, 2018 ; Gautam et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…These antibiotic mixes secreted by PGPRs conceal disease suppression of soilborne phytopathogens in rhizospheric region by inducing fungistasis, lysis of fungal mycelia and inhibition of spore germination (Adhya et al, 2018). A study by Kulimushi et al (2018) reported that antibiotics viz., phenazine, 2,4diacetylphloroglucinol (DAPG) produced by Pseudomonas sp. showed antagonistic activity against Meloidogyne incognita and Fusarium oxysporum f. sp.…”
Section: Antibiotics Productionmentioning
confidence: 99%
“…This variety is recommended at 800-1300 m above sea level. However, no report on its drought resistance exists [44]. The planting density of 50,000 plants per hectare was estimated for each farm.…”
Section: Water Use Efficiency and Yield Simulation By Csm-ceres-maize...mentioning
confidence: 99%